Biological and Pathological Implications of an Alternative ATP-Powered Proteasomal Assembly With Cdc48 and the 20S Peptidase - Esaki, Masatoshi; Johjima-Murata, Ai; Islam, Md. Tanvir; Ogura, Teru (Frontiers in Molecular Biosciences, 2018)
The ATP-powered protein degradation machinery plays essential roles in maintaining protein homeostasis in all organisms. Robust proteolytic activities are typically sequestered within protein complexes to avoid the fatal removal of essential proteins. Because the openings of proteolytic chambers are narrow, substrate proteins must undergo unfolding. AAA superfamily proteins (ATPases associated with diverse cellular activities) are mostly located at these openings and regulate protein degradation appropriately. The 26S proteasome, comprising 20S peptidase and 19S regulatory particles, is the major ATP-powered protein degradation machinery in eukaryotes. The 19S particles are composed of six AAA proteins and thirteen regulatory proteins, and bind to both ends of a barrel-shaped proteolytic chamber formed by the 20S peptidase. Several recent studies have reported that another AAA protein, Cdc48, can replace the 19S particles to form an alternative ATP-powered proteasomal complex, i.e., the Cdc48-20S proteasome. This review focuses on our current knowledge of this alternative proteasome and its possible linkage to amyotrophic lateral sclerosis.